Lightweight Verifiable Auditing for Outsourced Database in Cloud Computing - Kumar M.; Pasupuleti S.K. (My University, 2025)
Database outsourcing in Cloud Computing enables the data owner to store the data on cloud and assign the management to a cloud service provider (CSP), which provides various cloud services to the users. However, outsourcing database to cloud poses many challenges. One of the major concerns is confidentiality of the data. The general approach to tackle this issue is by encrypting the database before outsourcing, this helps in protecting confidentiality but poses a new problem of verifying the search results. We propose a lightweight verifiable auditing scheme for secure outsourcing of database, which encrypts the database and verifies search results with both parameters of correctness and completeness. We design our scheme based on a lightweight homomorphic encryption scheme (LHE) and efficient authenticated data structures to ensure the confidentiality and integrity of the database respectively. © 2018, Springer International Publishing AG.